Vert-zonal Differentiation in Monopolistic Competition - Francesco Di Comite; Jean-François Thisse; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
The pattern of trade observed from firm-product-country data calls for a new generation of models. To address the unexplained variation in the data, we propose a new model of monopolistic competition where varieties enter preferences non-symmetrically, capturing both horizontal and vertical differentiation in an unprecedented way. Together with a variable elasticity of substitution, competition effects, varying markups and prices across countries, this results in a tractable model whose predictions differ from existing ones. Using the population of Belgian exporters, our model succeeds in explaining the hitherto unexplained variation. The implications call for a re-thinking of earlier results and measurement practices.
Keywords: D43; F12; F14; L16; 330; Heterogeneous firms - Horizontal differentiation - Vertical differentiation - Monopolistic competition - non symmetric varieties; Produktdifferenzierung; Konsumentenverhalten; Monopolistischer Wettbewerb; Industrieökonomik; Belgien